Pengaruh Pemberian Dosis Pupuk Kandang Kambing dan Pupuk Urea Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays var.saccharata Sturt.) - Sri Yunaning; Junaidi Junaidi; Rasyadan Taufiq Probojati (Universitas Kadiri, 2022)
The growth and quality of sweet corn yields are believed to be influenced by environmental factors of soil fertility. Therefore, fertilization is one of the methods used to increase soil fertility for the growth and yield of sweet corn. Fertilization does not always give effective results as it is influenced by factors, including the correct application rate, method, and timing. This study was objected to determine the interaction effect between the dose of goat manure and the dose of urea fertilizer on the growth and yield of sweet corn plants. The study was conducted on rice fields with Alluvial soil types at the Faculty of Agriculture, Kadiri University, from March to April 2021. The experimental design used in this study was a 3 x 3 factorial randomized block design with 3 replications. Factor 1 was the dose of goat manure (D) consisting of 3 levels, namely D0 : 0 ha, D1: 10 tons/ha = 1.5 kg/plot, D2: 20 tons/ha = 3 kg/plot, while Factor 2 is the dose of urea (U) consisting of 3 levels, namely U1: 100 kg/ha = 15 grams/ plot, U2: 200 kg/ha = 30 gram/plot, U3: 300 kg/ha= 40 gram/plot. The results showed an interaction effect of the treatment dose of goat manure and urea on plant height at 30 days, stem diameter at 15 days and diameter of the cob. The dose treatment of goat manure and urea did not affect plant height at 15, 45 DAP, some leaves at 15, 30, and 45 DAP, stem diameter atÂ 30, and 45 DAP, length of cobs without husks, and weight of cobs without husks. Combining the treatment dose of goat manure 20ton/ha and urea 200 kg/ha resulted in the best growth. Corn production was not affected by dose treatment of goat manure and urea.Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh interaksi antara pemberian dosis pupuk kandang kambing dengan dosis pupuk urea terhadap pertumbuhan dan hasil tanaman jagung manis yang telah dilakukan pada lahan sawah dengan jenis tanah Alluvial di Fakultas Pertanian Universitas Kadiri, dimulai pada bulan Maret hingga April. Rancangan percobaan yang digunakan dalam penelitian ini adalah Rancangan Acak Kelompok (RAK) pola faktorial 3 x 3, dengan 3 ulangan. Faktor 1 adalah dosis pupuk kandang kambing (D) terdiri 3 level yaitu D0 : 0 ha, D1 : 10 ton/ha =1,5 kg/petak, D2 : 20 ton/ha = 3 kg/petak. Sedangkan ftor 2 adalah dosis urea (U) terdiri atas 3 level yaitu U1 : 100 kg/ha = 15 gram/petak, U2 : 200 kg/ha = 30 gram/petak, U3 : 300 kg/ha= 40 gram/petak. Hasil penelitan menunjukkan terjadi interaksi pengaruh perlakuan dosis pupuk kandang kambing dan urea terhadap tinggi tanaman umur 30 hari, diameter batang ummur 15 hari dan diameter tongkol tanpa kelobot. Perlakuan dosis pupuk kandang kambing dan urea tidak berpengaruh terhadap tinggi tanaman umur 15, 45 HST, jumlah daun umur 15, 30 dan 45 HST, diameter batang umur 30, dan 45 HST, panjang tongkol tanpa kelobot dan berat tongkol tanpa kelobot. Kombinasi perlakuan dosis pupuk kandang kambing 20ton/ha dan urea 200 kg/ha menghasilkan perttumbuhan paling baik.Produksi jagung tidak di pengaruhi oleh perlakuan dosis pupuk kandang kambing dan urea